2020
DOI: 10.1016/j.arth.2020.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Are Postoperative Hip Precautions Necessary After Primary Total Hip Arthroplasty Using a Posterior Approach? Preliminary Results of a Prospective Randomized Trial

Abstract: Background: It is unclear whether posterior hip precautions after primary total hip arthroplasty (THA) reduce the incidence of early postoperative dislocation. Methods: We performed a prospective randomized study to evaluate the effect of hip precautions on incidence of early dislocation after primary THA using a posterior approach. Between January 2016 and April 2019, 587 patients (594 hips) were consented and randomized into restricted or unrestricted groups. No significant demographic or surgical difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 29 publications
4
41
0
Order By: Relevance
“…In terms of post-operative orders or restrictions, variations still exist. For example, despite mounting evidence suggesting that removal of routine hip precautions after primary THA via posterior or anterolateral approach is safe (Dietz et al, 2019;Tetreault et al, 2020), 88% of respondents reported either standard or modified hip precautions as routine for this population. For sites where THA via an anterior approach was completed (62.4%), there was no consensus regarding use of routine precautions or restrictions.…”
Section: Discussionmentioning
confidence: 96%
“…In terms of post-operative orders or restrictions, variations still exist. For example, despite mounting evidence suggesting that removal of routine hip precautions after primary THA via posterior or anterolateral approach is safe (Dietz et al, 2019;Tetreault et al, 2020), 88% of respondents reported either standard or modified hip precautions as routine for this population. For sites where THA via an anterior approach was completed (62.4%), there was no consensus regarding use of routine precautions or restrictions.…”
Section: Discussionmentioning
confidence: 96%
“…Activity restrictions after HA and KA have been common [ 12 ], and restrictions following HA for at least 3 months have been widely practiced [ 13 ]. There are reports showing that departments with recommendations for activity restrictions have fewer dislocations than departments without restrictions [ 14 ], but other studies find that fewer lifestyle restrictions and precautions following HA seem to lead not to worse dislocation rates but to earlier and better resumption of activities and greater patient satisfaction, and these results appear to hold up for various surgical approaches [ 15 17 ]. Hip precautions may unnecessarily exacerbate patient anxiety and fear of dislocation following HA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In OT for HA patients, improving the performance of activities of daily living (ADL) is a central goal of the IRP [12]. Achieving this goal is essential for increasing individual independence, thereby improving the quality of life (QOL) for HA patients [13].…”
Section: Introductionmentioning
confidence: 99%